2013
DOI: 10.1097/meg.0b013e32835d913b
|View full text |Cite
|
Sign up to set email alerts
|

Early increase in α-fetoprotein for predicting unfavorable clinical outcomes in patients with advanced hepatocellular carcinoma treated with sorafenib

Abstract: Early increase in AFP predicted PD and poorer survival and may thus be a useful biomarker in patients with advanced HCC who receive sorafenib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 33 publications
3
61
0
1
Order By: Relevance
“…Prospective phase Ⅲ trial [126] CEC/ CECP al [74] did not find a significant link between pretreatment AFP levels and tumor response in patients with advanced HCC treated with sorafenib. However, an early increase in AFP levels correlates with poorer outcome with shorter OS and PFS [74] .…”
Section: Poorer Prognosismentioning
confidence: 88%
See 2 more Smart Citations
“…Prospective phase Ⅲ trial [126] CEC/ CECP al [74] did not find a significant link between pretreatment AFP levels and tumor response in patients with advanced HCC treated with sorafenib. However, an early increase in AFP levels correlates with poorer outcome with shorter OS and PFS [74] .…”
Section: Poorer Prognosismentioning
confidence: 88%
“…However, an early increase in AFP levels correlates with poorer outcome with shorter OS and PFS [74] . Japanese groups proposed the lens culinaris agglutinin reactive AFP (AFP-L3), an isoform of AFP, as a good diagnostic and prognostic biomarker for HCC [75][76][77] .…”
Section: Poorer Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent studies have investigated plasma biomarkers as potential markers of response to sorafenib (and other antiangiogenic therapies), such as α-fetoprotein [52][53][54][55], and additional research is ongoing. There are also some small studies that suggest that sorafenib AEs (e.g., skin toxicity and hypertension) may be markers of clinical efficacy and that the pattern of disease progression on sorafenib treatment may predict the postprogression prognosis [27,56].…”
Section: Identifying Markers Of Tumor Response May Help To Guide Soramentioning
confidence: 99%
“…In patients with advanced HCC treated with either sorafenib, transarterial chemoembolization, hepatic artery infusional chemotherapy or concurrent chemoradiotherapy, an early reduction of AFP was found to be a predictor of positive outcome (22)(23)(24)(25). Furthermore, the early elevation of AFP was shown to be a predictor of unfavorable outcome in patients with advanced HCC treated with sorafenib (26). In addition, it was demonstrated that a low serum AFP level (≤50 ng/ml) was a favorable predictor for patients treated with intravenous 5-fluorouracil and subcutaneous recombinant interferon-α-2b (27), suggesting a predictive value of AFP in patients receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 97%